Conserving genetic diversity in the honeybee: Comments on Harpur et al. (2012). Issue 12 (28th May 2013) - De la, Pilar; Jaffé, Rodolfo; Muñoz, Irene; Serrano, José; Moritz, Robin F. A.; Kraus, F. Bernhard
Abstract The article by Harpur et al. (2012) 'Management increases genetic diversity of honey bees via admixture' concludes that '…honey bees do not suffer from reduced genetic diversity caused by management and, consequently, that reduced genetic diversity is probably not contributing to declines of managed Apis mellifera populations'. In the light of current honeybee and beekeeping declines and their consequences for honeybee conservation and the pollination services they provide, we would like to express our concern about the conclusions drawn from the results of Harpur et al. (2012). While many honeybee management practices do not imply admixture, we are convinced that the large‐scale genetic homogenization of admixed populations could drive the loss of valuable local adaptations. We also point out that the authors did not account for the extensive gene flow that occurs between managed and wild/feral honeybee populations and raise concerns about the data set used. Finally, we caution against underestimating the importance of genetic diversity for honeybee colonies and highlight the importance of promoting the use of endemic honeybee subspecies in apiculture.